Influence of Boron Adding on the Acoustic Materials Signature Curves for Computing of Surface Acoustic Wave Velocities of Ti64 Alloys - Al-Sayad, Y.; Hadjoub, Z.; Doghmane, A. (Металлофизика и новейшие технологии, 2018)
The effect of Boron admixture with five different concentrations x = 0.0, 0.04, 0.09, 0.30 and 0.55% wt. B on elastic properties of Ti–6Al–4V alloy is investigated. The values of velocities of propagating surface acoustic wave as well as bulk wave for additional structures are deduced. As found, with the increasing of Boron content in Ti–6Al–4V alloy, its acoustic material signature (Young’s modulus E, shear modulus G, bulk modulus B), longitudinal velocities, and shear velocities increase from 113 to 126 GPa, from 42.5 to 47.4 GPa, from 110.8 to 123.5 GPa, from 6148 to 6492 m/s, from 3097 to 3171 m/s, respectively. Using angular spectrum model, we calculate the reflectance function and the acoustic materials signature of Ti–6Al–4V–xB, which show an oscillatory behaviour. The spectral treatment of these signatures provides the exact definition of Rayleigh wave velocity. Исследовано влияние примеси бора при пяти значениях концентрации x = 0,0, 0,04, 0,09, 0,30 и 0,55% масс. B на упругие свойства сплава Ti–6Al–4V. Определены значения скоростей распространяющейся поверхностной акустической волны, а также объёмной акустической волны для дополнительных структур. Установлено, что при увеличении содержания бора в сплаве Ti–6Al–4V акустические характеристики материала (модуль Юнга E, модуль сдвига G, объёмный модуль B), продольные скорости и скорости сдвига увеличиваются от 113 до 126 ГПа, от 42,5 до 47,4 ГПа, от 110,8 до 123,5 ГПа, от 6148 до 6492 м/с, от 3097 до 3171 м/с соответственно. С использованием модели углового спектра вычислены функция отражения и акустические характеристики материала Ti–6Al–4V–xB, которые проявляют осциллирующее поведение. Спектральная обработка этих характеристик позволяет точно определить скорость волны Рэлея. Досліджено вплив домішки Бору за п’ятьох значень концентрації x = 0,0, 0,04, 0,09, 0,30 та 0,55% мас. B на пружні властивості стопу Ti–6Al–4V. Визначено значення швидкостей поширюваної поверхневої акустичної хвилі, а також об’ємної акустичної хвилі для додаткових структур. Встановлено, що при збільшенні вмісту Бору в стопі Ti–6Al–4V акустичні характеристики матеріялу (модуль Юнґа E, модуль зсуву G, об’ємний модуль B), поздовжні швидкості та швидкості зсуву збільшуються від 113 до 126 ГПа, від 42,5 до 47,4 ГПа, від 110,8 до 123,5 ГПа, від 6148 до 6492 м/с, від 3097 до 3171 м/с відповідно. З використанням моделю кутового спектру розраховано функцію відбивання й акустичні характеристики матеріялу Ti–6Al–4V–xB, які проявляють осцилівну поведінку. Спектральна обробка цих характеристик забезпечує можливість точного визначення швидкости Релейової хвилі.